Efficacy and safety of simoctocog alfa (Nuwiq®) in patients with severe hemophilia A: a review of clinical trial data from the GENA program. (June 2019) - Lissitchkov, Toshko; Klukowska, Anna; Pasi, John; Kessler, Craig M.; Klamroth, Robert; Liesner, Raina J.; Belyanskaya, Larisa; Walter, Olaf; Knaub, Sigurd; Bichler, Johann; Jansen, Martina; Oldenburg, Johannes
Simoctocog alfa (human-cl rhFVIII, Nuwiq®) is a 4th generation recombinant FVIII (rFVIII), without chemical modification or fusion with any other protein/fragment. Nuwiq® is produced in a human embryonic kidney cell line (HEK293F), which ensures human-specific post-translational protein processing. Nuwiq® was evaluated in seven prospective clinical studies in 201 adult and pediatric previously treated patients (PTPs) with severe hemophilia A. The NuProtect study in 110 previously untreated patients (PUPs) is ongoing. The mean half-life of Nuwiq® was 15.1–17.1 h in PTP studies with adults and adolescents, and 12.5 h in children aged 2–12 years. Clinical trials in PTPs demonstrated the efficacy and safety of Nuwiq® in the prevention and treatment of bleeds and as surgical prophylaxis. In the NuPreviq study of pharmacokinetic (PK)-guided personalized prophylaxis in 66 adult PTPs, 83% of patients had no spontaneous bleeds during 6 months of personalized prophylaxis and 57% were treated ⩽2 per week. No FVIII inhibitors were detected in PTPs after treatment with 43, 267 injections and >80 million IU of Nuwiq®. Interim data for 66 PUPs with ⩾20 exposure days to Nuwiq® in NuProtect demonstrated a low cumulative high-titer inhibitor rate of 12.8% [actual incidence 12.1% (8/66)] and convincing efficacy and safety.